The Children’s Songs Composition: A Contribution to Fill in The Absence of Children’s Songs in Indonesian Preschool Education - Wadiyo, Wadiyo; Utomo, Udi; Haryono, Slamet; Wiyoso, Joko (Resital: Jurnal Seni Pertunjukan, 2021)
The song is one of the teaching media used by preschool teachers around the globe. Indonesian preschool teachers face a rising problem: the government regulates a standard curriculum where the educational song is compulsory. Yet, there is no concern to facilitate and fill in the absence of children's educational songs. This study aims to unveil the creative process of non-music education graduate teachers in composing educational songs as required by the curriculum. This study employs a qualitative design based on a case study of thirty-three teachers from eleven different preschools in Semarang, Central Java, Indonesia. The researchers analyze the preschools' curriculum, teachers' interviews, field observations, and documentation. The findings show that teachers can use their creativity to create songs with educational messages projected in a collective poetry singing performance. Poetry singing allows students' aesthetic skills development through continuous song probe and response between teachers and students.